2004
DOI: 10.1016/s0006-3495(04)74256-3
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Predictions of the Structure and Function of G-Protein-Coupled Receptors: Validation for Bovine Rhodopsin

Abstract: G-protein-coupled receptors (GPCRs) are involved in cell communication processes and with mediating such senses as vision, smell, taste, and pain. They constitute a prominent superfamily of drug targets, but an atomic-level structure is available for only one GPCR, bovine rhodopsin, making it difficult to use structure-based methods to design receptor-specific drugs. We have developed the MembStruk first principles computational method for predicting the three-dimensional structure of GPCRs. In this article we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 58 publications
2
98
0
Order By: Relevance
“…The MembStruk and HierDock protocols have also been applied to other GPCRs including bovine rhodopsin receptor [10], human dopamine D2 receptor [13], human β2 adrenergic receptor [14] and several olfactory receptors [15][16][17]. In each case the key interactions observed in the experiments are identified from our prediction, validating that these methods can predict the 3D structures of the proteins and the binding sites of strongly bound ligands to these sites.…”
Section: Experimentally Verifying the Predictionssupporting
confidence: 54%
See 2 more Smart Citations
“…The MembStruk and HierDock protocols have also been applied to other GPCRs including bovine rhodopsin receptor [10], human dopamine D2 receptor [13], human β2 adrenergic receptor [14] and several olfactory receptors [15][16][17]. In each case the key interactions observed in the experiments are identified from our prediction, validating that these methods can predict the 3D structures of the proteins and the binding sites of strongly bound ligands to these sites.…”
Section: Experimentally Verifying the Predictionssupporting
confidence: 54%
“…This work builds upon our recent studies in which we first predicted the 3-D structures of mouse MrgC11 (mMrgC11) and MrgA1 (mMrgA1) receptors using the MembStruk computational method [9,10]. These structures were validated by predicting the binding sites and energies for several tetrapeptides, identifying key residues, and then experimentally confirming the expected changes in binding resulting from mutations of these residues.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The only GPCR with an experimental 3D crystal structure is bovine rhodopsin (15,16), making this the best structure for validating MembStruk. Trabanino et al (6) showed that the TM regions of the MembStruk-predicted structure for rhodopsin agree with the crystal structure, to 2.85 Å CRMS (rms deviation in alpha carbon coordinates) for all of the main chain atoms. This good agreement with the crystal structure indicates that the MembStruk procedure predicts the helical regions reasonably well, without using any knowledge of the crystal structure.…”
Section: Methodsmentioning
confidence: 72%
“…Using the multiple sequence alignment as input, the TM regions were predicted using TM2ndS procedure. 10 The hydrophobic maximum was chosen as the central residue (referred to as the centroid) for each helix that divides the area under the hydrophobicity curve equally. The centroid for each helix is positioned to be in the same xy plane (the midpoint of the lipid).…”
Section: Prediction Of the Tm Regions And Hydrophobic Centersmentioning
confidence: 99%